Icatibant, an inhibitor of bradykinin receptor 2, for hereditary angioedema attacks: prospective experimental single-cohort study - Campos, Regis Albuquerque; Valle, Solange Oliveira Rodrigues; França, Alfeu Tavares; Cordeiro, Elisabete; Serpa, Faradiba Sarquis; Mello, Yara Ferreira; Malheiros, Teresinha; Toledo, Eliana; Mansour, Elie; Fusaro, Gustavo; Grumach, Anete Sevciovic (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Hereditary angioedema (HAE) with C1 inhibitor deficiency manifests as recurrent episodes of edema involving the skin, upper respiratory tract and gastrointestinal tract. It can be lethal due to asphyxia. The aim here was to evaluate the response to therapy for these attacks using icatibant, an inhibitor of the bradykinin receptor, which was recently introduced into Brazil. DESIGN AND SETTING: Prospective experimental single-cohort study on the efficacy and safety of icatibant for HAE patients. METHODS: Patients with a confirmed HAE diagnosis were enrolled according to symptoms and regardless of the time since onset of the attack. Icatibant was administered in accordance with the protocol that has been approved in Brazil. Symptom severity was assessed continuously and adverse events were monitored. RESULTS: 24 attacks in 20 HAE patients were treated (female/male 19:1; 19-55 years; median 29 years of age). The symptoms were: subcutaneous edema (22/24); abdominal pain (15/24) and upper airway obstruction (10/24). The time taken until onset of relief was: 5-10 minutes (5/24; 20.8%); 10-20 (5/24; 20.8%); 20-30 (8/24; 33.4%); 30-60 (5/24; 20.8%); and 2 hours (1/24; 4.3%). The time taken for complete resolution of symptoms ranged from 4.3 to 33.4 hours. Adverse effects were only reported at injection sites. Mild to moderate erythema and/or feelings of burning were reported by 15/24 patients, itching by 3 and no adverse effects in 6. CONCLUSION: HAE type I patients who received icatibant responded promptly; most achieved improved symptom severity within 30 minutes. Local adverse events occurred in 75% of the patients.